1986
DOI: 10.1046/j.1468-2982.1986.0604205.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 5–HIAA in Migraine: Evidence of Lowered Excretion in Young Adult Females

Abstract: Urinary 5-hydroxyindoleacetic acid (5-HIAA) and homovanillic acid (HVA) were determined in 44 young adult migraine patients (35 women, 9 men) between attacks and in 33 healthy controls (23 women, 10 men). HVA excretion was equivalent in all groups. 5-HIAA was unaltered in men but was significantly decreased in female migraine patients when compared with their sex-matched controls (-31%, p less than 0.01). No relationship was found between 5-HIAA excretion and the various characteristics of migraine, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…3 It has also been reported that urinary 5-HIAA excretion is decreased in both migraine types. 16 Our present data do not indicate any impairment of the degradation activity of serotonin in migraine with aura, since the levels of serotonin and 5-HIAA were strongly intercorrelated in a pattern similar to that of the controls. In migraine without aura and tension headache, however, no such significant correlation was observed, which may suggest some anomaly in serotonin catabolism.…”
Section: Commentssupporting
confidence: 49%
“…3 It has also been reported that urinary 5-HIAA excretion is decreased in both migraine types. 16 Our present data do not indicate any impairment of the degradation activity of serotonin in migraine with aura, since the levels of serotonin and 5-HIAA were strongly intercorrelated in a pattern similar to that of the controls. In migraine without aura and tension headache, however, no such significant correlation was observed, which may suggest some anomaly in serotonin catabolism.…”
Section: Commentssupporting
confidence: 49%
“…As discussed previously, there is experimental evidence to show that jaw-opening and closing reflexes are modulated by central serotonin In particular, it has been shown in the cat that stimulation of the raphe magnus inhibits the jaw-opening reflex evoked by tooth pulp stimulation (17). Modifications of serotonin metabolism have been reported in menstrual migraine (8,22), which has been ascribed to the physiological withdrawal of oestrogen during the premenstrual phase of the cycle (23). Several other neurochemical modifications have been observed during the premenstrual phase not only in women complaining of menstrual migraine, but also in those presenting with the premenstrual syndrome.…”
Section: Table 1 Temporalis Es2 (Mean ± Sem) At 01 and 2 Hz In The mentioning
confidence: 95%
“…Two other studies found a declining tendency in urinary excretion of 5‐HIAA. Bousser et al presented evidence that urine 5‐HIAA excretion was significantly reduced in 35 adult young female migraineurs between migraine attacks. Milovanovic et al demonstrated the similar tendency of reduced urinary 5‐HIAA with a small sample (18 migraines).…”
Section: Neurotransmitters and Receptorsmentioning
confidence: 86%